LOSS OF VIGOR IN CONILON COFFEE SEEDLINGS DUE TO THE APPLICATION OF GRANULAR FUNGICIDE FOR SOIL (Nucleus, 2011)
Coffee leaf rust (Hemileia vastatrix) is the disease with the greater potential to do damage to coffee plantations. Diversified products are available for its control, for example, there are fungicides of granular from that are applied in the soil, such as cyproconazole+thiamethoxam. But there is a secondary effect associated with those products called 'tonic effect' which is characterized by the promotion of a high vigor in the plant, increasing the foliage and also the green tone of the leaves. However, this tonic effect can cause metabolic problems in the plant. The objective of this study was to evaluate the influence of the application of a granular fungicide applied in the soil (cyproconazole+thiamethoxam) in the vigor of seedlings of conilon coffee clones that compose the cultivar 'Vitória Incaper 8142', in greenhouse conditions. All the clones, grown in greenhouse, showed a reduction in their vigor when the application of the granular fungicide was done.